L’ épitaphe LSAG2 436-437 n° 3a de Gardiki Phthiotidos au pays des Ainianes - Helly, Bruno (Tekmeria, 2025)
In the second edition of the Local Scripts of Archaic Greece, published in 1990, there was an epitaph in the Thessalian dialect whose transcription was preserved in the archives of the eminent English epigraphist L. H. Jeffery, along with a facsimile of the text and a provenance listed as "Phthiotis." It was not until 2007, thanks to the presentation made by A. Matthaiou at the colloquium organized by the University of Thessaly in Volos in honor of Professor Christian Habicht, that we obtained precise information about the stele bearing this text, its exact provenance, and its place of conservation in the collection of inscriptions housed at the Museum of Lamia. Access to this now well-identified monument has made it possible to study it thoroughly, to verify the inscription, to conduct a more precise analysis of the text (which had been incorrectly parsed in previous editions), and to interpret it as the earliest known and, for the moment, the only archaeological testimony of the settlement of the Ainianes in the middle valley of the Sperchios—a territory to which they gave their name, the Ainis.